2016
DOI: 10.18632/oncotarget.12662
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the anatomical parameters for normal tissue sparing in the prone position radiotherapy with small sized left breasts

Abstract: Prone position radiotherapy for a small (< 750 cm3) breast is controversial because of the variable benefits for the irradiated heart volume. The objective anatomical parameters related with chest wall shape that can determine the heart dose sparing patients in the prone position.Twenty-one patients underwent CT-simulation in supine and prone position. Dose volume parameters were compared and the objective indexes such as the Haller index, anthropometric index, mid-sternum thickness, and central lung distance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 25 publications
1
12
0
1
Order By: Relevance
“…In our study, all enrolled patients had a seroma clarity score <3, and we delineated the TB based on only the surgical clips. In addition, several studies have verified that the prone position has a significant advantage over the supine position in the conformity index of the targets (27,33). On the other hand, our results further indicated that compared with the supine position, the prone position led to a greater CTV intersection (greater by 5.79 cm 3 ).…”
Section: Discussionsupporting
confidence: 66%
“…In our study, all enrolled patients had a seroma clarity score <3, and we delineated the TB based on only the surgical clips. In addition, several studies have verified that the prone position has a significant advantage over the supine position in the conformity index of the targets (27,33). On the other hand, our results further indicated that compared with the supine position, the prone position led to a greater CTV intersection (greater by 5.79 cm 3 ).…”
Section: Discussionsupporting
confidence: 66%
“…Moreover, Kim et al . 17 verified that although there was no difference in the HI between the supine and prone positions, yet a significant advantage in the prone position was found in the CI. Breast and regional lymph nodes can be treated with an equal or better dose distribution in the target volumes in the prone position than in the supine position.…”
Section: Discussionmentioning
confidence: 70%
“… 16 also confirmed that for patients who underwent WBI, a small but statistically significant difference was evident in the whole breast CTV between the prone and supine positions (57 cc lower in the prone position). However, for patients with small breasts (<750 cm 3 ) who underwent radiotherapy in the prone position, no obvious variations in the breast target volume were found between the supine and prone positions 17 . In our study, the enrolled patients with breast volumes less than 750 cm 3 comprised 63% of all patients.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Among the maneuvers that allow the chest wall to be separated from the heart are irradiation in the prone position as well as techniques for monitoring respiratory movement [ 73 , 74 , 75 ].…”
Section: Risk Reduction Strategiesmentioning
confidence: 99%